Advances in gastrointestinal endoscopy in practical terms - Celiński, Krzysztof; Fornal, Rafał; Dworzański, Tomasz; Słomka, Maria; Mądro, Agnieszka (Polish Journal of Public Health, 2012)
For many years, endoscopic procedures such as gastroscopy or colonoscopy have allowed early detection of gastrointestinal dysfunctional lesions. However, technological progress in gastrointestinal endoscopy, driven by need to precisely differentiate tumor from normal tissues and inflammatory lesions, is constantly observed. The following accepted and verified, new endoscopic techniques have been described in the research: capsule endoscopy, assisted balloon enteroscopy, endoscopic ultrasound, endoscopy with magnification image and the new electronic systems improving image quality. Possibilities and limitations of each method have been discussed and practical aspects of their application have been highlighted.